Epidemiology of Haemoparasites Causing Infections in Cattle of Junagadh, Gujarat, India - Thakre, Bhupendrakumar J; Singh, Vivek Kumar; Brahmbhatt, Nilima N; Gamit, Krishna C; Parmar, Vijay L; Bilwal, Avinash K; Kachara, Sohil H (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The current investigation used microscopy to determine the incidence and epidemiology of key haemoprotozoans, including Theileria,  Babesia, Trypanosoma, and rickettsia Anaplasma in cattle from the Junagadh region of Western Gujarat, India. Whole blood samples (948)  from cattle were obtained between January 2023 and May 2024 at several places, including the Veterinary Clinical Complex, Gaushala,  Pashumela, Panjarapole, and farmers’ homes. According to microscopic examination of samples, 22.46% (213/948) of the population  had haemoparasitic infections. In particular, the prevalence rates for mixed infections, Babesia spp., Trypanosoma spp., Anaplasma spp. and Theileria spp. were 2.00%, 2.42%, 5.69%, 1.26%, and 11.07%, respectively. Cattle above the age of 4 years had the highest frequency  of haemoparasitic infections (35.37%), followed by cattle between the ages of 1-4 years (16.50%) and < 1 year (10.89%). Male animals  (17.24%) and female animals (24.45%) showed a significantly different prevalence. Compared to cattle from organised farms (11.91%),  the prevalence of infection was much greater in unorganised farms (28.96%) due to poor flooring, fractured walls, and poor sanitation.  The infection rate of crossbred animals was greater (33.89%) than that of the Gir breed (13.53%), indicating that crossbred animals are  more vulnerable than native breeds. The summer (31.01%) had the highest frequency of infection, followed by the monsoon (16.55%)  and winter (16.63%) seasons. The results of this study highlight the importance of haemoparasites to cattle health in this area.
Keywords: Cattle; Epidemiology; Junagadh; Prevalence; VCC; Western Gujarat